(untitled) - Bhagwati, Jagdish N. (Delhi, 1970)
This Book Chronicles The Indian Experience With Industrialization In The Two Decades Since Independence In 1947 Which Has Evoked Reactions Which Appear To Have Regressed From Great Optimism To Exaggerated Despair. No Jacket, Ex-Library Book. Boards Rubbed. Spine Slightly Damaged On The Lower End...